ADMINISTRATIVE AND LEGAL RESPONSIBILITY AS A MEANS OF ENSURING ENVIRONMENTAL LAW AND ORDER - Yerezhepkyzy, R.; Bitabarova, Zh.A.; Bekisheva, S.D.; Yessetova, S.K.; Saduakasova, L.K. (Habaršy - A̋l-Farabi atyndag̣y K̦azak̦ memlekettik ụlttyk̦ universiteti.Zan̦ seriâsy, 2024)
This article examines the institution of administrative and legal accountability for environmental violations in the context of upholding environmental law and order. The objective of the article is to identify specific features and uncover new facets of the institution of administrative and legal responsibility for environmental offenses. The study focused on the following tasks: characterizing this institution, analyzing administrative offenses in the field of environmental protection and natural resource management, identifying their specific characteristics as offenses, and developing strategies for improving their detection and prevention. The proposed hypothesis is the importance of administrative and legal responsibility for ensuring environmental law and order. The article has scientific (the author's definition of an administrative offense in the field of environmental protection, the use of natural resources, the established differences between administrative and criminal offenses in the environmental sphere contributes to the development of the theory of environmental and administrative law) and practical significance (the recommendations are aimed at improving Kazakh legislation, optimizing the system of administrative penalties). The core outcomes involve the development of a definition for administrative offenses within environmental protection and natural resource usage, as well as the identification of their unique characteristics and their differentiation from other offense types. The study concludes with a recommendation to review the current system of administrative penalties. The value of these findings and conclusions is highlighted by their contribution to the theory of environmental and administrative law. Keywords: Administrative offenses in the field of environmental protection, criminal liability, environmental offense, environmental criminal offense, environmental criminal offense.